Self-heat-dissipation bus duct and temperature field optimization design method thereof
By using materials such as copper alloys, graphene, aluminum borate whiskers, and nano-titanium dioxide in the busbar trunking and optimizing the temperature field design, the problem of insufficient heat dissipation during high-load operation of the busbar trunking was solved, achieving efficient heat dissipation and improved stability.
Patent Information
- Application Number
- CN202510945510.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-09
- Publication Date
- 2025-10-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing busbar cooling methods are mostly natural cooling or simple air cooling, which are difficult to meet the needs of high-load operation, resulting in excessive temperature, affecting performance and service life, and may even cause safety accidents.
A self-heating busbar composed of materials such as copper alloy, graphene, aluminum borate whiskers, and nano-titanium dioxide is used. Combined with temperature field optimization design methods, the heat dissipation performance is improved by optimizing the distribution of graphene, aluminum borate whiskers, and nano-titanium dioxide and improving the heat sink structure.
It significantly improves the heat dissipation and thermal conductivity of the busbar trunking, ensuring safety and stability under high load operation, extending service life, reducing temperature, and improving operational stability.
Smart Images

Figure CN120879440A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of busbar technology, specifically to a self-heating busbar and its temperature field optimization design method. Background Technology
[0002] Busbar trunking is widely used in modern power systems, its main function being the transmission of electrical energy. However, with the continuous increase in electrical load, busbar trunking generates a large amount of heat during operation. If heat dissipation is not timely, the busbar trunking temperature will become too high, affecting its performance and service life, and may even lead to safety accidents. Existing busbar trunking heat dissipation methods are mostly natural heat dissipation or simple air cooling, with limited heat dissipation effect, making it difficult to meet the needs of high-load operation. Therefore, developing a busbar trunking with efficient heat dissipation performance and its temperature field optimization design method is of significant practical importance.
[0003] Based on this, a self-heating busbar trunking and its temperature field optimization design method are designed. Summary of the Invention
[0004] The purpose of this invention is to provide a self-heating busbar trunking and its temperature field optimization design method to solve the problems mentioned in the background art.
[0005] To achieve the above objectives, the present invention provides the following technical solution:
[0006] A self-heating busbar trunking comprises the following components in parts by weight:
[0007] Copper alloy: 70-80 parts;
[0008] Graphene: 5-10 parts;
[0009] Aluminum borate whiskers: 3-8 parts;
[0010] Nano titanium dioxide: 2-5 parts;
[0011] Epoxy resin: 10-15 parts.
[0012] Preferably, the graphene is prepared by the following method:
[0013] S1. Raw material preparation: Select high-purity graphite powder with a purity of ≥99.9% and put it into a ball mill;
[0014] S2. Ball milling treatment: Add an appropriate amount of ethanol as a dispersant to the ball mill, with a rotation speed of 300-500 rpm and a ball milling time of 10-15 hours, so that the particle size of the ball-milled graphite powder is less than 1 micrometer.
[0015] S3. Oxidation treatment: Disperse the ball-milled graphite powder in a mixed solution of concentrated sulfuric acid and hydrogen peroxide, with a volume ratio of sulfuric acid to hydrogen peroxide of 3:1. React in a water bath at 40-60℃ for 4-6 hours to fully oxidize the graphite powder and form graphite oxide.
[0016] S4. Exfoliation treatment: Disperse graphene oxide in deionized water and use an ultrasonic processor for exfoliation treatment. The ultrasonic power is 300-500W and the treatment time is 1-2 hours to obtain a graphene dispersion.
[0017] S5. Drying and Collection: Centrifuge the graphene dispersion at a speed of 8000-10000 rpm for 10-15 minutes. Collect the precipitated graphene and dry it to obtain graphene powder.
[0018] Preferably, the method for preparing the aluminum borate whiskers is as follows:
[0019] S1. Raw material mixing: Mix boric acid and aluminum hydroxide in a molar ratio of 1:1, add an appropriate amount of deionized water and stir evenly to form a uniform slurry;
[0020] S2. Hydrothermal reaction: The mixed slurry is placed in a hydrothermal reactor and reacted for 12-18 hours at a temperature of 180-220℃ and a pressure of 1.5-2.0MPa.
[0021] S3. Washing and drying: After the reaction is complete, the product is washed with deionized water until neutral, and then dried in an oven at 80-100℃ for 10-12 hours to obtain aluminum borate whiskers.
[0022] Preferably, the preparation method of the nano-titanium dioxide is as follows:
[0023] S1. Raw material dissolution: Dissolve tetrabutyl titanate in anhydrous ethanol and stir until homogeneous to form a uniform solution.
[0024] S2. Hydrolysis reaction: Under stirring, deionized water is slowly added to the solution to control the hydrolysis rate and allow the solution to gradually form a gel.
[0025] S3. Drying and calcination: Dry the gel in an oven at 60-80℃ for 10-12 hours, and then calcine it in a muffle furnace at 300-500℃ for 2-3 hours to obtain nano-titanium dioxide powder.
[0026] Preferably, the method for preparing the self-heating busbar includes the following steps:
[0027] S1. Raw material mixing: Mix copper alloy, graphene, aluminum borate whiskers, nano titanium dioxide and epoxy resin evenly.
[0028] S2. Molding process: Place the mixed raw materials into the mold and mold them at a temperature of 150-180℃ and a pressure of 10-15MPa for 10-15 minutes.
[0029] S3. Post-processing: After molding, the busbar trunking is naturally cooled at room temperature, and then surface treatment is performed to ensure a smooth surface and reduce heat loss.
[0030] A method for optimizing the temperature field of a self-heating busbar trunking includes the following steps:
[0031] S1. Model Establishment
[0032] S1.1 Geometric Modeling: Using 3D modeling software, such as SolidWorks or AutoCAD, to create a geometric model of the busbar trunking, including but not limited to the main structure of the busbar trunking, heat sinks, and insulation layers.
[0033] Ensure that the size and shape of the model match the actual busbar, accurate to the millimeter level;
[0034] S1.2 Material parameter setting: Based on the material composition of the busbar, set the thermal physical parameters such as thermal conductivity, specific heat capacity and density of each material;
[0035] The thermal conductivity of copper alloys is 380-400 W / (m·K), the specific heat capacity is 380-400 J / (kg·K), and the density is 8900-9000 kg / m³. 3 ;
[0036] Graphene has a thermal conductivity of 5000-6000 W / (m·K), a specific heat capacity of 700-800 J / (kg·K), and a density of 2200-2300 kg / m³. 3 ;
[0037] Aluminum borate whiskers have a thermal conductivity of 300-350 W / (m·K), a specific heat capacity of 800-900 J / (kg·K), and a density of 3000-3200 kg / m³. 3 ;
[0038] Nano-titanium dioxide has a thermal conductivity of 80-100 W / (m·K), a specific heat capacity of 700-800 J / (kg·K), and a density of 4200-4300 kg / m³. 3 .
[0039] The thermal conductivity of epoxy resin is 0.2-0.3 W / (m·K), the specific heat capacity is 1200-1300 J / (kg·K), and the density is 1200-1300 kg / m³. 3 ;
[0040] S2, Boundary Condition Setting
[0041] S2.1 Convection heat transfer coefficient: The convective heat transfer coefficient between the busbar surface and the air is set to 10-20 W / (m²). 2 ·K);
[0042] S2.2 Ambient temperature: Set the ambient temperature to 20-30℃;
[0043] S2.3 Current Density: Set the current density inside the busbar trunking to 10-20 A / mm². 2 ;
[0044] S3, Mesh Generation
[0045] S3.1 Mesh type selection: Select unstructured mesh for division to adapt to the complex geometry and internal structure of the busbar trunking;
[0046] S3.2 Mesh density setting: In the hot spots of the busbar trunking, in areas with high current density, and near the heat sink, set a finer mesh with a mesh unit size of 1-2mm;
[0047] In other areas, a coarser grid is used, with grid cell size of 5-10mm;
[0048] Ensure that the number of grid cells is no less than 1 million to guarantee the accuracy of the simulation results;
[0049] S4, Numerical Simulation
[0050] S4.1 Software selection: Use finite element analysis software, either ANSYS or COMSOL Multiphysics, for numerical simulation;
[0051] S4.2 Equation Selection: The steady-state heat conduction equation and the convection heat transfer equation are used to calculate the temperature distribution of the busbar under different operating conditions;
[0052] Steady-state heat conduction equation:
[0053] Where k is thermal conductivity, T is temperature, and Q is the heat source term, which is the heat generated by the current;
[0054] Convection heat transfer equation: h(TT) env )=q
[0055] Where h is the convective heat transfer coefficient, Tenv is the ambient temperature, and q is the surface heat flux;
[0056] S4.3 Simulation parameter settings: Set the initial temperature of the simulation to the ambient temperature, and set the simulation time step to 0.1-0.5 seconds;
[0057] S4.4 Simulation Operation: Start the simulation, calculate the temperature distribution of the busbar under different operating conditions, and record the simulation results, including but not limited to temperature distribution diagrams and hot spot temperature values;
[0058] S5, Optimized Design
[0059] S5.1 Hotspot Analysis: Based on the simulation results, analyze the hotspot areas of the busbar trunking and determine the parts that need to be optimized;
[0060] S5.2 Material Distribution Optimization: Adjust the distribution position and concentration of graphene, aluminum borate whiskers and nano titanium dioxide to concentrate them in hot spots and improve heat dissipation.
[0061] S5.3 Structural optimization: Increase the number and area of heat sinks, optimize the shape and layout of heat sinks, and optimize the shape of busbar trunking to make it more conducive to heat dissipation;
[0062] S5.4 Parameter Adjustment: Based on the optimized design, reset the material parameters and boundary conditions, perform numerical simulation, compare the temperature distribution results before and after optimization, and evaluate the optimization effect;
[0063] S6. Experimental Verification
[0064] S6.1 Experimental preparation: Based on the optimized design results, manufacture busbar samples for the experiment and prepare experimental equipment, including but not limited to temperature sensors, thermal imagers, and current sources.
[0065] S6.2 Experimental Conditions: The experimental ambient temperature is set at 25℃, and the current density is set at 15A / mm². 2 Temperature sensors are installed in the hot spots of the busbar trunking to record temperature changes;
[0066] S6.3 Experimental Operation: Start the current source to make the busbar run under high load, use a thermal imager to take a temperature distribution map of the busbar, and record the hot spot temperature values;
[0067] S6.4 Result Analysis: Compare the experimental results with the simulation results of the optimization design to verify the effectiveness of the optimization design. If the experimental results are consistent with the simulation results, it indicates that the optimization design is effective; if there is a large deviation, the optimization scheme needs to be further adjusted.
[0068] Compared with the prior art, the present invention has the following beneficial effects:
[0069] 1. This invention significantly improves the heat dissipation and thermal conductivity of busbar trunking by adding graphene, aluminum borate whiskers, and nano-titanium dioxide. At the same time, by adopting a temperature field optimization design method, the heat dissipation structure can be precisely optimized according to the actual structure and operating conditions of the busbar trunking, further improving the heat dissipation effect. Compared with traditional busbar trunking, the self-heating busbar trunking of this invention can effectively reduce the temperature during high-load operation, improve operational stability and reliability, and extend service life, resulting in significant economic and social benefits.
[0070] 2. This invention significantly improves the heat dissipation performance of the busbar trunking by adding and optimizing the design of graphene, aluminum borate whiskers, and nano-titanium dioxide, ensuring its safety and stability under high load operation and exhibiting high-efficiency heat dissipation performance.
[0071] 3. The addition of graphene, aluminum borate whiskers, and nano titanium dioxide not only improves heat dissipation performance but also enhances the mechanical strength of the busbar trunking, extending its service life and resulting in high mechanical strength. Attached Figure Description
[0072] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the embodiments of the invention to explain the invention and do not constitute a limitation thereof.
[0073] In the attached diagram:
[0074] Figure 1 A flowchart illustrating an exemplary embodiment of the present invention is shown; Detailed Implementation
[0075] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0076] A self-heating busbar trunking according to this embodiment comprises the following components in parts by weight:
[0077] Copper alloy: 70-80 parts;
[0078] Graphene: 5-10 parts;
[0079] Aluminum borate whiskers: 3-8 parts;
[0080] Nano titanium dioxide: 2-5 parts;
[0081] Epoxy resin: 10-15 parts.
[0082] The method for preparing graphene in this embodiment is as follows:
[0083] S1. Raw material preparation: Select high-purity graphite powder with a purity of ≥99.9% and put it into a ball mill;
[0084] S2. Ball milling treatment: Add an appropriate amount of ethanol as a dispersant to the ball mill, with a rotation speed of 300-500 rpm and a ball milling time of 10-15 hours, so that the particle size of the ball-milled graphite powder is less than 1 micrometer.
[0085] S3. Oxidation treatment: Disperse the ball-milled graphite powder in a mixed solution of concentrated sulfuric acid and hydrogen peroxide, with a volume ratio of sulfuric acid to hydrogen peroxide of 3:1. React in a water bath at 40-60℃ for 4-6 hours to fully oxidize the graphite powder and form graphite oxide.
[0086] S4. Exfoliation treatment: Disperse graphene oxide in deionized water and use an ultrasonic processor for exfoliation treatment. The ultrasonic power is 300-500W and the treatment time is 1-2 hours to obtain a graphene dispersion.
[0087] S5. Drying and Collection: Centrifuge the graphene dispersion at a speed of 8000-10000 rpm for 10-15 minutes. Collect the precipitated graphene and dry it to obtain graphene powder.
[0088] The preparation method of aluminum borate whiskers in this embodiment is as follows:
[0089] S1. Raw material mixing: Mix boric acid and aluminum hydroxide in a molar ratio of 1:1, add an appropriate amount of deionized water and stir evenly to form a uniform slurry;
[0090] S2. Hydrothermal reaction: The mixed slurry is placed in a hydrothermal reactor and reacted for 12-18 hours at a temperature of 180-220℃ and a pressure of 1.5-2.0MPa.
[0091] S3. Washing and drying: After the reaction is complete, the product is washed with deionized water until neutral, and then dried in an oven at 80-100℃ for 10-12 hours to obtain aluminum borate whiskers.
[0092] The preparation method of nano-titanium dioxide in this embodiment is as follows:
[0093] S1. Raw material dissolution: Dissolve tetrabutyl titanate in anhydrous ethanol and stir until homogeneous to form a uniform solution.
[0094] S2. Hydrolysis reaction: Under stirring, deionized water is slowly added to the solution to control the hydrolysis rate and allow the solution to gradually form a gel.
[0095] S3. Drying and calcination: Dry the gel in an oven at 60-80℃ for 10-12 hours, and then calcine it in a muffle furnace at 300-500℃ for 2-3 hours to obtain nano-titanium dioxide powder.
[0096] The method for preparing the self-heating busbar in this embodiment includes the following steps:
[0097] S1. Raw material mixing: Mix copper alloy, graphene, aluminum borate whiskers, nano titanium dioxide and epoxy resin evenly.
[0098] S2. Molding process: Place the mixed raw materials into the mold and mold them at a temperature of 150-180℃ and a pressure of 10-15MPa for 10-15 minutes.
[0099] S3. Post-processing: After molding, the busbar trunking is naturally cooled at room temperature, and then surface treatment is performed to ensure a smooth surface and reduce heat loss.
[0100] A method for optimizing the temperature field of a self-heating busbar trunking includes the following steps:
[0101] S1. Model Establishment
[0102] S1.1 Geometric Modeling: Using 3D modeling software, such as SolidWorks or AutoCAD, to create a geometric model of the busbar trunking, including but not limited to the main structure of the busbar trunking, heat sinks, and insulation layers.
[0103] Ensure that the size and shape of the model match the actual busbar, accurate to the millimeter level;
[0104] S1.2 Material parameter setting: Based on the material composition of the busbar, set the thermal physical parameters such as thermal conductivity, specific heat capacity and density of each material;
[0105] The thermal conductivity of copper alloys is 380-400 W / (m·K), the specific heat capacity is 380-400 J / (kg·K), and the density is 8900-9000 kg / m³. 3 ;
[0106] Graphene has a thermal conductivity of 5000-6000 W / (m·K), a specific heat capacity of 700-800 J / (kg·K), and a density of 2200-2300 kg / m³. 3 ;
[0107] Aluminum borate whiskers have a thermal conductivity of 300-350 W / (m·K), a specific heat capacity of 800-900 J / (kg·K), and a density of 3000-3200 kg / m³. 3 ;
[0108] Nano-titanium dioxide has a thermal conductivity of 80-100 W / (m·K), a specific heat capacity of 700-800 J / (kg·K), and a density of 4200-4300 kg / m³. 3 .
[0109] The thermal conductivity of epoxy resin is 0.2-0.3 W / (m·K), the specific heat capacity is 1200-1300 J / (kg·K), and the density is 1200-1300 kg / m³. 3 ;
[0110] S2, Boundary Condition Setting
[0111] S2.1 Convection heat transfer coefficient: The convective heat transfer coefficient between the busbar surface and the air is set to 10-20 W / (m²). 2 ·K);
[0112] S2.2 Ambient temperature: Set the ambient temperature to 20-30℃;
[0113] S2.3 Current Density: Set the current density inside the busbar trunking to 10-20 A / mm². 2 ;
[0114] S3, Mesh Generation
[0115] S3.1 Mesh type selection: Select unstructured mesh for division to adapt to the complex geometry and internal structure of the busbar trunking;
[0116] S3.2 Mesh density setting: In the hot spots of the busbar trunking, in areas with high current density, and near the heat sink, set a finer mesh with a mesh unit size of 1-2mm;
[0117] In other areas, a coarser grid is used, with grid cell size of 5-10mm;
[0118] Ensure that the number of grid cells is no less than 1 million to guarantee the accuracy of the simulation results;
[0119] S4, Numerical Simulation
[0120] S4.1 Software selection: Use finite element analysis software, either ANSYS or COMSOL Multiphysics, for numerical simulation;
[0121] S4.2 Equation Selection: The steady-state heat conduction equation and the convection heat transfer equation are used to calculate the temperature distribution of the busbar under different operating conditions;
[0122] Steady-state heat conduction equation:
[0123] Where k is thermal conductivity, T is temperature, and Q is the heat source term, which is the heat generated by the current;
[0124] Convection heat transfer equation: h(TT) env )=q
[0125] Where h is the convective heat transfer coefficient, Tenv is the ambient temperature, and q is the surface heat flux;
[0126] S4.3 Simulation parameter settings: Set the initial temperature of the simulation to the ambient temperature, and set the simulation time step to 0.1-0.5 seconds;
[0127] S4.4 Simulation Operation: Start the simulation, calculate the temperature distribution of the busbar under different operating conditions, and record the simulation results, including but not limited to temperature distribution diagrams and hot spot temperature values;
[0128] S5, Optimized Design
[0129] S5.1 Hotspot Analysis: Based on the simulation results, analyze the hotspot areas of the busbar trunking and determine the parts that need to be optimized;
[0130] S5.2 Material Distribution Optimization: Adjust the distribution position and concentration of graphene, aluminum borate whiskers and nano titanium dioxide to concentrate them in hot spots and improve heat dissipation.
[0131] S5.3 Structural optimization: Increase the number and area of heat sinks, optimize the shape and layout of heat sinks, and optimize the shape of busbar trunking to make it more conducive to heat dissipation;
[0132] S5.4 Parameter Adjustment: Based on the optimized design, reset the material parameters and boundary conditions, perform numerical simulation, compare the temperature distribution results before and after optimization, and evaluate the optimization effect;
[0133] S6. Experimental Verification
[0134] S6.1 Experimental preparation: Based on the optimized design results, manufacture busbar samples for the experiment and prepare experimental equipment, including but not limited to temperature sensors, thermal imagers, and current sources.
[0135] S6.2 Experimental Conditions: The experimental ambient temperature is set at 25℃, and the current density is set at 15A / mm². 2 Temperature sensors are installed in the hot spots of the busbar trunking to record temperature changes;
[0136] S6.3 Experimental Operation: Start the current source to make the busbar run under high load, use a thermal imager to take a temperature distribution map of the busbar, and record the hot spot temperature values;
[0137] S6.4 Result Analysis: Compare the experimental results with the simulation results of the optimization design to verify the effectiveness of the optimization design. If the experimental results are consistent with the simulation results, it indicates that the optimization design is effective; if there is a large deviation, the optimization scheme needs to be further adjusted.
[0138] Example 1:
[0139] Preparation of self-heating busbar trunking:
[0140] Raw material mixing: Mix 75 parts copper alloy, 7 parts graphene, 5 parts aluminum borate whiskers, 3 parts nano titanium dioxide and 12 parts epoxy resin evenly.
[0141] Molding process: Place the mixed raw materials into the mold and mold them at a temperature of 150-180℃ and a pressure of 10-15MPa for 10-15 minutes.
[0142] Post-processing: After molding, the busbar trunking is allowed to cool naturally at room temperature, and then surface treatment is performed to ensure a smooth surface and reduce heat loss.
[0143] Temperature field optimization design method for self-heating busbars:
[0144] S1. Model Establishment:
[0145] Use SolidWorks to create the geometric model of the busbar, including but not limited to the main structure, heat sinks, and insulation layers;
[0146] The thermal conductivity of copper alloy is set to 380 W / (m·K), that of graphene is 5000 W / (m·K), that of aluminum borate whiskers is 300 W / (m·K), that of nano titanium dioxide is 80 W / (m·K), and that of epoxy resin is 0.2 W / (m·K).
[0147] S2, Boundary Condition Setting:
[0148] The convective heat transfer coefficient is set to 15 W / (m²). 2 K), ambient temperature 25℃, current density 15A / mm 2 ;
[0149] S3, Mesh Generation:
[0150] The mesh was generated using ANSYS, with the mesh element size of 1mm in hotspot areas and 5mm in other areas, for a total of 1.2 million mesh elements.
[0151] S4. Numerical Simulation:
[0152] Start the simulation and calculate the temperature distribution of the busbar under different operating conditions;
[0153] Record the simulation results, including temperature distribution maps and hotspot temperature values;
[0154] S5, Optimized Design:
[0155] The concentration of graphene was increased from 7% to 8%, and concentrated in areas with high current density.
[0156] Increase the number of heat sinks and adjust the spacing between them from 10mm to 5mm;
[0157] The shape of the tank was optimized by changing it from a rectangle to a trapezoid to increase the heat dissipation area.
[0158] The material parameters and boundary conditions were reset, and numerical simulations were performed to compare the temperature distribution results before and after optimization.
[0159] S6. Experimental verification:
[0160] Based on the optimized design results, a busbar sample for experimental use was manufactured.
[0161] At an ambient temperature of 25°C, the current density is 15 A / mm². 2 The experiment was conducted under the following conditions;
[0162] Use a thermal imager to capture temperature distribution maps and record the temperature values of hot spots;
[0163] Experimental results show that the optimized busbar coolant temperature is 20-30℃ lower than that before optimization when operating under high load, and the heat dissipation effect is significantly improved.
[0164] Example 2:
[0165] Preparation of self-heating busbar trunking:
[0166] Raw material mixing: Mix 78 parts copper alloy, 8 parts graphene, 6 parts aluminum borate whiskers, 4 parts nano titanium dioxide and 14 parts epoxy resin evenly.
[0167] Molding process: Place the mixed raw materials into the mold and mold them at a temperature of 160-190℃ and a pressure of 12-16MPa for 12-16 minutes.
[0168] Post-processing: After molding, the busbar trunking is allowed to cool naturally at room temperature, and then surface treatment is performed to ensure a smooth surface and reduce heat loss.
[0169] Temperature field optimization design method for self-heating busbars:
[0170] S1. Model Establishment:
[0171] Use SolidWorks to create the geometric model of the busbar, including but not limited to the main structure, heat sinks, and insulation layers;
[0172] The thermal conductivity of copper alloy is set to 390 W / (m·K), that of graphene is 5200 W / (m·K), that of aluminum borate whiskers is 320 W / (m·K), that of nano titanium dioxide is 90 W / (m·K), and that of epoxy resin is 0.25 W / (m·K).
[0173] S2, Boundary Condition Setting:
[0174] The convective heat transfer coefficient is set to 18 W / (m²). 2 The ambient temperature was 28℃, and the current density was 18A / mm². 2 ;
[0175] S3, Mesh Generation:
[0176] The mesh was generated using ANSYS, with the mesh element size of 1.6 mm in hotspot areas and 6 mm in other areas, for a total of 1.3 million mesh elements.
[0177] S4. Numerical Simulation:
[0178] Start the simulation and calculate the temperature distribution of the busbar under different operating conditions;
[0179] Record the simulation results, including temperature distribution maps and hotspot temperature values;
[0180] S5, Optimized Design:
[0181] The concentration of graphene was increased from 8% to 10%, and concentrated in areas with high current density.
[0182] Increase the number of heat sinks and adjust the spacing between them from 10mm to 4mm;
[0183] The shape of the tank was optimized by changing it from a rectangle to a trapezoid to increase the heat dissipation area.
[0184] The material parameters and boundary conditions were reset, and numerical simulations were performed to compare the temperature distribution results before and after optimization.
[0185] S6. Experimental verification:
[0186] Based on the optimized design results, a busbar sample for experimental use was manufactured.
[0187] At an ambient temperature of 28°C, the current density is 18 A / mm². 2 The experiment was conducted under the following conditions;
[0188] Use a thermal imager to capture temperature distribution maps and record the temperature values of hot spots;
[0189] Experimental results show that the optimized busbar trunking has a temperature that is 25-35℃ lower than that before optimization when operating under high load, and the heat dissipation effect is significantly improved.
[0190] Example 3:
[0191] Preparation of self-heating busbar trunking:
[0192] Raw material mixing: Mix 80 parts copper alloy, 10 parts graphene, 8 parts aluminum borate whiskers, 5 parts nano titanium dioxide and 15 parts epoxy resin evenly.
[0193] Molding process: Place the mixed raw materials into the mold and mold them at a temperature of 170-200℃ and a pressure of 14-186MPa for 14-18 minutes.
[0194] Post-processing: After molding, the busbar trunking is allowed to cool naturally at room temperature, and then surface treatment is performed to ensure a smooth surface and reduce heat loss.
[0195] Temperature field optimization design method for self-heating busbars:
[0196] S1. Model Establishment:
[0197] Use SolidWorks to create the geometric model of the busbar, including but not limited to the main structure, heat sinks, and insulation layers;
[0198] The thermal conductivity of copper alloy is set to 400 W / (m·K), that of graphene is 5500 W / (m·K), that of aluminum borate whiskers is 350 W / (m·K), that of nano titanium dioxide is 100 W / (m·K), and that of epoxy resin is 0.3 W / (m·K).
[0199] S2, Boundary Condition Setting:
[0200] The convective heat transfer coefficient is set to 20 W / (m²). 2 K), ambient temperature 30℃, current density 20A / mm 2 ;
[0201] S3, Mesh Generation:
[0202] The mesh was generated using ANSYS, with the mesh element size of 2mm in hotspot areas and 7mm in other areas, for a total of 1.4 million mesh elements.
[0203] S4. Numerical Simulation:
[0204] Start the simulation and calculate the temperature distribution of the busbar under different operating conditions;
[0205] Record the simulation results, including temperature distribution maps and hotspot temperature values;
[0206] S5, Optimized Design:
[0207] The concentration of graphene was increased from 10% to 12%, and concentrated in areas with high current density.
[0208] Increase the number of heat sinks and adjust the spacing between them from 10mm to 3mm;
[0209] The shape of the tank was optimized by changing it from a rectangle to a trapezoid to increase the heat dissipation area.
[0210] The material parameters and boundary conditions were reset, and numerical simulations were performed to compare the temperature distribution results before and after optimization.
[0211] S6. Experimental verification:
[0212] Based on the optimized design results, a busbar sample for experimental use was manufactured.
[0213] At an ambient temperature of 30°C, the current density is 20 A / mm². 2 The experiment was conducted under the following conditions;
[0214] Use a thermal imager to capture temperature distribution maps and record the temperature values of hot spots;
[0215] Experimental results show that the optimized busbar coolant temperature is 30-40℃ lower than that before optimization when operating under high load, and the heat dissipation effect is significantly improved.
[0216] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
[0217] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A self-heating busbar trunking, characterized in that, The composition includes the following parts by weight: Copper alloy: 70-80 parts; Graphene: 5-10 parts; Aluminum borate whiskers: 3-8 parts; Nano titanium dioxide: 2-5 parts; Epoxy resin: 10-15 parts.
2. The self-heating busbar trunking according to claim 1, characterized in that, The graphene is prepared as follows: S1. Raw material preparation: Select high-purity graphite powder with a purity of ≥99.9% and put it into a ball mill; S2. Ball milling treatment: Add an appropriate amount of ethanol as a dispersant to the ball mill, with a rotation speed of 300-500 rpm and a ball milling time of 10-15 hours, so that the particle size of the ball-milled graphite powder is less than 1 micrometer. S3. Oxidation treatment: Disperse the ball-milled graphite powder in a mixed solution of concentrated sulfuric acid and hydrogen peroxide, with a volume ratio of sulfuric acid to hydrogen peroxide of 3:
1. React in a water bath at 40-60℃ for 4-6 hours to fully oxidize the graphite powder and form graphite oxide. S4. Exfoliation treatment: Disperse graphene oxide in deionized water and use an ultrasonic processor for exfoliation treatment. The ultrasonic power is 300-500W and the treatment time is 1-2 hours to obtain a graphene dispersion. S5. Drying and Collection: Centrifuge the graphene dispersion at a speed of 8000-10000 rpm for 10-15 minutes. Collect the precipitated graphene and dry it to obtain graphene powder.
3. The self-heating busbar trunking according to claim 1, characterized in that, The method for preparing the aluminum borate whiskers is as follows: S1. Raw material mixing: Mix boric acid and aluminum hydroxide in a molar ratio of 1:1, add an appropriate amount of deionized water and stir evenly to form a uniform slurry; S2. Hydrothermal reaction: The mixed slurry is placed in a hydrothermal reactor and reacted for 12-18 hours at a temperature of 180-220℃ and a pressure of 1.5-2.0MPa. S3. Washing and drying: After the reaction is complete, the product is washed with deionized water until neutral, and then dried in an oven at 80-100℃ for 10-12 hours to obtain aluminum borate whiskers.
4. The self-heating busbar trunking according to claim 1, characterized in that, The preparation method of the nano-titanium dioxide is as follows: S1. Raw material dissolution: Dissolve tetrabutyl titanate in anhydrous ethanol and stir until homogeneous to form a uniform solution. S2. Hydrolysis reaction: Under stirring, deionized water is slowly added to the solution to control the hydrolysis rate and allow the solution to gradually form a gel. S3. Drying and calcination: Dry the gel in an oven at 60-80℃ for 10-12 hours, and then calcine it in a muffle furnace at 300-500℃ for 2-3 hours to obtain nano-titanium dioxide powder.
5. A self-heating busbar trunking according to claim 1, characterized in that, The method for preparing the self-heating busbar includes the following steps: S1. Raw material mixing: Mix copper alloy, graphene, aluminum borate whiskers, nano titanium dioxide and epoxy resin evenly. S2. Molding process: Place the mixed raw materials into the mold and mold them at a temperature of 150-180℃ and a pressure of 10-15MPa for 10-15 minutes. S3. Post-processing: After molding, the busbar trunking is naturally cooled at room temperature, and then surface treatment is performed to ensure a smooth surface and reduce heat loss.
6. A method for optimizing the temperature field of a self-heating busbar trunking, characterized in that, Includes the following steps: S1. Model Establishment S1.1 Geometric Modeling: Using 3D modeling software, such as SolidWorks or AutoCAD, to create a geometric model of the busbar trunking, including but not limited to the main structure of the busbar trunking, heat sinks, and insulation layers. Ensure that the size and shape of the model match the actual busbar, accurate to the millimeter level; S1.2 Material parameter setting: Based on the material composition of the busbar, set the thermal physical parameters such as thermal conductivity, specific heat capacity and density of each material; The thermal conductivity of copper alloys is 380-400 W / (m·K), the specific heat capacity is 380-400 J / (kg·K), and the density is 8900-9000 kg / m³. 3 ; Graphene has a thermal conductivity of 5000-6000 W / (m·K), a specific heat capacity of 700-800 J / (kg·K), and a density of 2200-2300 kg / m³. 3 ; Aluminum borate whiskers have a thermal conductivity of 300-350 W / (m·K), a specific heat capacity of 800-900 J / (kg·K), and a density of 3000-3200 kg / m³. 3 ; Nano-titanium dioxide has a thermal conductivity of 80-100 W / (m·K), a specific heat capacity of 700-800 J / (kg·K), and a density of 4200-4300 kg / m³. 3 . The thermal conductivity of epoxy resin is 0.2-0.3 W / (m·K), the specific heat capacity is 1200-1300 J / (kg·K), and the density is 1200-1300 kg / m³. 3 ; S2, Boundary Condition Setting S2.1 Convection heat transfer coefficient: The convective heat transfer coefficient between the busbar surface and the air is set to 10-20 W / (m²). 2 ·K); S2.2 Ambient temperature: Set the ambient temperature to 20-30℃; S2.3 Current Density: Set the current density inside the busbar trunking to 10-20 A / mm². 2 ; S3, Mesh Generation S3.1 Mesh type selection: Select unstructured mesh for division to adapt to the complex geometry and internal structure of the busbar trunking; S3.2 Mesh density setting: In the hot spots of the busbar trunking, in areas with high current density, and near the heat sink, set a finer mesh with a mesh unit size of 1-2mm; In other areas, a coarser grid is used, with grid cell size of 5-10mm; Ensure that the number of grid cells is no less than 1 million to guarantee the accuracy of the simulation results; S4, Numerical Simulation S4.1 Software selection: Use finite element analysis software, either ANSYS or COMSOL Multiphysics, for numerical simulation; S4.2 Equation Selection: The steady-state heat conduction equation and the convection heat transfer equation are used to calculate the temperature distribution of the busbar under different operating conditions; Steady-state heat conduction equation: Where k is thermal conductivity, T is temperature, and Q is the heat source term, which is the heat generated by the current; Convection heat transfer equation: h(TT) env )=q Where h is the convective heat transfer coefficient, Tenv is the ambient temperature, and q is the surface heat flux; S4.3 Simulation parameter settings: Set the initial temperature of the simulation to the ambient temperature, and set the simulation time step to 0.1-0.5 seconds; S4.4 Simulation Operation: Start the simulation, calculate the temperature distribution of the busbar under different operating conditions, and record the simulation results, including but not limited to temperature distribution diagrams and hot spot temperature values; S5, Optimized Design S5.1 Hotspot Analysis: Based on the simulation results, analyze the hotspot areas of the busbar trunking and determine the parts that need to be optimized; S5.2 Material Distribution Optimization: Adjust the distribution position and concentration of graphene, aluminum borate whiskers and nano titanium dioxide to concentrate them in hot spots and improve heat dissipation. S5.3 Structural optimization: Increase the number and area of heat sinks, optimize the shape and layout of heat sinks, and optimize the shape of busbar trunking to make it more conducive to heat dissipation; S5.4 Parameter Adjustment: Based on the optimized design, reset the material parameters and boundary conditions, perform numerical simulation, compare the temperature distribution results before and after optimization, and evaluate the optimization effect; S6. Experimental Verification S6.1 Experimental preparation: Based on the optimized design results, manufacture busbar samples for the experiment and prepare experimental equipment, including but not limited to temperature sensors, thermal imagers, and current sources. S6.2 Experimental Conditions: The experimental ambient temperature is set at 25℃, and the current density is set at 15A / mm². 2 Temperature sensors are installed in the hot spots of the busbar trunking to record temperature changes; S6.3 Experimental Operation: Start the current source to make the busbar run under high load, use a thermal imager to take a temperature distribution map of the busbar, and record the hot spot temperature values; S6.4 Result Analysis: Compare the experimental results with the simulation results of the optimization design to verify the effectiveness of the optimization design. If the experimental results are consistent with the simulation results, it indicates that the optimization design is effective; if there is a large deviation, the optimization scheme needs to be further adjusted.